Penggunaan Game Android Terhadap Kemampuan Mengenali Rumus Kimia pada Mahasiswa Calon Guru Sekolah Dasar - Erfan, Muhammad; Maulyda, Mohammad Archi (Universitas Hamzanwadi, 2020)
Entrepreneurship learning and support for the family environment give positive impact in building students' knowledge, interest and skills in the field of entrepreneurship so that they can produce graduates who are creative, innovative,productive,reliable,quality, independent, self-controlled and competitive.This study aims to determine the influence of knowledge and family environment on student entrepreneurial attitudes.This study is a descriptive exploratory study with 56 respondents as students of biology education at Mandalika University of Education.The research instrument used is a closed questionnaire with degraded answers according to the likert scale and has been validated (expert validation).The research data analysis used was inferential statistics with multiple linear regression at 5% significance level.The results of the studyÂ showed that (1) the knowledge and attitudes of student entrepreneurship had a percentage of 88.00% and 78.35% in the Very Good category,while environmental support had a percentage of 68.20 in Good category; (2)there is an effect of knowledge and family environment on student entrepreneurial attitudes (F=7,245 p=0,002<0,05); (3) knowledge and family environment simultaneously affect the entrepreneurial attitude of students by 21,5% and the remaining is influenced by other variables or factors (R square=0,215). Therefore it can be concluded that the collaboration of student knowledge about entrepreneurship and entrepreneurial family environment activities has a positive role in developing student entrepreneurial attitudes.